Clostridial myonecrosis, haemolytic anaemia, hepatopathy, osteitis and transient hypertrophic cardiomyopathy after intramuscular injection in a Thoroughbred gelding. Issue 5 (11th March 2013) - Anderson, FL; Secombe, CJ; Lester, GD
<x xml:space="preserve">Abstract</x> A 9‐year‐old Thoroughbred gelding was presented for swelling over the left neck and inappetence. There was recent history of intramuscular administration of flunixin meglumine into the left neck. On examination, there was evidence of focal myositis, anaemia, haemolysis and pigmenturia. Culture of aspirated fluid from the left side of the neck produced a heavy growth of a Clostridium species. Complications of infection included haemolytic anaemia, hepatopathy, osteitis and transient hypertrophic cardiomyopathy. Treatment included intravenous fluid therapy, antibiotics, anti‐inflammatory drugs, blood transfusion and surgical debridement. There was complete resolution of clinical, haematological, biochemical and echocardiographic abnormalities, and the horse returned to ridden work. This report highlights the complications that can arise from clostridial myonecrosis, including the effect on the myocardium.